PENGARUH LATIHAN JUMP TO BOX TERHADAP POWER OTOT TUNGKAI PADA CLUB SIBAM KARATE PEKANBARU - Loyo C. Panggabean; Ramadi Ramadi; Ali Mandan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The problem in this research is that their strength is very low, and it may also cause them to perform poorly. Because without good power, the technique itself is not enough to win the match. The title of this research is